Effectiveness of Online Recruitment & Selection Process: A Comprehensive Assessment (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The purpose of this paper is to give an overallassessment of effectiveness of using internet to recruit and select people.Online recruitment is effective in terms of saving cost of recruitment andselection. Effectiveness of online recruitment and selection depicts that itsaves time to hire and reduces recruitment cost. E-recruitment, also known asonline recruitment, is the practice of using technology and in particularWeb-based resources for tasks involved with finding, attracting, assessing,interviewing and hiring new personnel.